Application of Theories, Techniques, Methods and Approaches to Develop Second Language Skills-a Study Based on Transition From Schooling to College - Jeya Gowri, K; Ilankumaran, M (International Journal of Engineering and Technology, 2018)
English is not just an official language in India, but also the language of mediation, higher education, science and technology. It is stated that India follows an improper curriculum pattern which is clear in the case of English language teaching, because the concept is failure in attaining the supreme result over the proficiency in language. Therefore, English Language Teaching and Learning in India is considered to be low in quality, according to the Indian Educational System. This hindrance can be ignored through proper curriculum pattern. The objective of this paper is to identify the connection between behaviour, anxiety and enthusiasm of high school and tertiary level students in learning English and obtaining the proficiency in second language skills. Second Language Learners fail to acquire the basic verbal skills from the school level. For the positive transition from the tertiary to the college, there should be a strong motivation from the side of education system as well as the people around the students. According to Vincent Tinto there are three stages that the students encounter in their academic life, they are separation, transition and incorporation. The paper also explores the transition period of the students psychologically, and offers remedial measures to come out of the confusion. It explores the theories, techniques, methods and approaches for imparting the second language skills during the transitional period of the students. The education system, adult learning and transition theories, problems and challenges have also been discussed in the paper.Â